Multilayer and Thin Transparent Conducting Oxide Fabrication Using RF Magnetron Sputtering on Flexible Substrates - Swami, Sanjay Kumar; Barman, Bidyut; Kumar, Anuj; Dutta, Viresh (Organic Materials, 2023)
In this work, the fabrication of multilayered transparent conductive oxides (TCOs), ZnO–Ag–ZnO (Z-TCO) and AZO–Ag–AZO (AZ-TCO), on flexible polyethylene terephthalate (PET) substrate using radio frequency (RF) magnetron sputtering is reported, with the optical and electrical properties comparable to those of the commercially available Sn-doped indium oxide (ITO) on the PET substrate. The growth of Z-TCO and AZ-TCO layers on PET (with surface roughness ~5 – 7 nm) shows similar surface characteristics to that on the glass substrate. The multilayered Z-TCO and AZ-TCO (total thickness ~70 nm) with 10 nm of Ag thickness (named Z-2 and AZ-2, respectively) exhibit a maximum transparency of 82.7% and 86.4%, at 515 and 498 nm, respectively. The AZ-2 layer has a lower electrical resistivity of 3.92 × 10−5 Ω cm with a lower sheet resistance of 5.6 Ω/sq, whereas for ITO on PET these values are 2.62 × 10−4 Ω cm and 14.5 Ω/sq, respectively. The AZ-2 layer also gives an excellent figure of merit (FoM) of 21.3 × 10−3 Ω−1, which is better than the FoM for ITO PET (17.3 × 10−3 Ω−1). Therefore, the flexible multilayer TCOs prepared using RF magnetron sputtering on PET substrates on a large area can have better optoelectronic properties than commercial flexible ITO coating and can be used in flexible optoelectronic devices.
Keywords: flexible substrates; multilayered TCO; magnetron sputtering; electrical resistivity; figure of merit